Plasma Exosomal miRNA-122-5p and miR-300-3p as Potential Markers for Transient Ischaemic Attack in Rats - Li, Dong-Bin; Liu, Jing-Li; Wang, Wei; Luo, Xiu-Mei; Zhou, Xia; Li, Jin-Pin; Cao, Xiao-Li; Long, Xiao-Hong; Chen, Jia-Gui; Qin, Chao (Frontiers in Aging Neuroscience, 2018)
Background: Differentiation of transient ischaemic attack（TIA）from ischaemic stroke within the thrombolysis time window is difficult. Although TIA may be diagnosed within this window, the latest imaging technologies are complex and costly. Serum markers, which are non-invasive, rapid and economic, are used for diagnosis and prognosis of various diseases. Exosome-derived miRNA markers for TIA are unknown. Methods: We examined focal brain ischaemia produced by occlusion of the middle cerebral artery (MCAo) for 5 min, 10 min, and 2 hours in rats. Exosomal miRNAs with consistent trends in cerebrospinal fluid (CSF) and plasma were identified by deep sequencing and quantitative real-time polymerase chain reaction (qRT-PCR). The areas under the curve (AUC) of the receiver operating characteristic (ROC) curve were used to evaluate the diagnostic accuracy of these miRNAs for TIA in rats. Results: Rno-miR-122-5p and rno-miR-300-3p were selected. Plasma exosomal rno-miR-122-5p was significantly downregulated in 10 min ischaemic rats compared with control and 5 min plasma. Plasma exosomal rno-miR-300-3p was significantly upregulated in 5 min ischaemic rats compared with control, 10 min and 2 hour rats. Plasma and CSF levels of these miRNAs were correlated. ROC analysis showed high AUC values for rno-miR-122-5p (0.960) and rno-miR-300-3p (0.970) in the 10 min and 5 min rats, respectively, compared with controls. Conclusions: Plasma exosomal rno-miR-122-5p and rno-miR-300-3p may be blood-based TIA biomarkers.